2019
DOI: 10.35219/foodtechnology.2019.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the antioxiant peptides production from goat milk casein hydrolyzed by alcalase and papain using respons surface methodology

Abstract: Antioxidant peptides are widely used in many fields due to their biological activities such as anti-cancer, anti-induction and anti-aging. However, little information is available concerning the peptides production by enzymatic hydrolysis of casein from goat milk. In this study, response surface methodology (RSM) was applied to optimize the conditions of the hydrolysis of goat milk casein by proteases (alcalase in combination with papain) to increase the antioxidant activity of the peptides. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It was found that the hydrolysis conditions that led the highest antioxidative activity of the produced peptides were 55°C, pH 7.5, substrate concentration of 3.0%, an enzyme/substrate of 4.0%, a ratio of Alcalase/papain of 1/3 and a reaction time of 180 min [409]. Later, the optimization of hydrolysis condition of goat milk casein using mixtures of Alcalase/papain was optimized via response surface methodology [410]. The optimal reaction conditions were 61°C, enzyme/substrate ratio of 5.6%, and a combi-protease papain: Alcalase of 1.8.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the hydrolysis conditions that led the highest antioxidative activity of the produced peptides were 55°C, pH 7.5, substrate concentration of 3.0%, an enzyme/substrate of 4.0%, a ratio of Alcalase/papain of 1/3 and a reaction time of 180 min [409]. Later, the optimization of hydrolysis condition of goat milk casein using mixtures of Alcalase/papain was optimized via response surface methodology [410]. The optimal reaction conditions were 61°C, enzyme/substrate ratio of 5.6%, and a combi-protease papain: Alcalase of 1.8.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The optimal reaction conditions were 61°C, enzyme/substrate ratio of 5.6%, and a combi-protease papain: Alcalase of 1.8. This led a 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity increased 1.17 folds compared to un-optimized conditions [410].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…After centrifugation at 5000×g for 15 minutes, the supernatant was collected and adjusted to pH 8.3 with NaOH (1 mol/L) and centrifuged at 5000×g for 15 minutes. The supernatant was collected as the whey sample for the determination of antioxidant activity (Shu et al, 2019).…”
Section: Microorganism and Growth Mediummentioning
confidence: 99%